The Complementary Relationship between Target Costing and Value Chain In The Public Corporations Of The Jordanian Industrial Sector: An Empirical Study (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to study the target costing and value chain with their complimentary relationship in reducing product costs, meeting the needs of customer, and achieving strategic competitive advantage for manufacturing corporations in response to face international competition, technological development and continuous changing expectations of customers.    No doubt, the target costing and value chain both currently occupy a great deal of the attention of managers and accountants at the manufacturing corporations due to the significance to insure their continuity, growth and development. This significance has been the main motive to examine the role of target costing and value chain in a sample of public corporations of the industrial sector in Jordan .The corporations in the industrial sector have been selected in this research because the practices related to target costing and value chain have not been given the required attention in the previous research and studies.The data was collected by means of a questionaire handed to a sample from the Jordanian manufacturing corporations to test the four null hypotheses. The results overall indicate that the sampled corporations have the appropriate environment to the application of target costing approach, there exist a role to the mentioned approaches in reducing cost and there is a relevant relationship between the two approaches. Also, these results clearly show that there are some statistically significant relationships between target rosting and value chain approaches at the jordanian manufacturing corporations. Finally,The result of the analysis have led to reject the null hypotheses (1) to (4) of the research and fully accepted the alternative ones.